Three-dimensional hierarchical and superhydrophobic graphene gas sensor with good immunity to humidity - Wu, Jin (2020)
Superhydrophobic reduced graphene oxide (RGO) with unique 3D hierarchical structures is synthesized by exploiting one-step spark plasma sintering (SPS) within 60 s for high-performance NO2 detection. The effective removal of oxygenated groups and generation of 3D hierarchical structures in SPS render the RGO superhydrophobic. The superhydrophobicity makes the fabricated RGO sensor exceptionally immune to high relative humidity (RH). Specifically, the RGO sensor exhibits a response degradation less than 5.5% to 1 ppm NO2 when the RH increases from 0% to 70%. Importantly, an integrated microheater array is employed to remarkably activate the RGO-based NO2 sensor, boosting the sensitivity. Consequently, the NO2 sensor displays a high sensitivity (25.5 ppm-1) and an extremely low limit of detection (9.1 ppb). The boosted NO2 sensing performance is attributed to superhydrophobicity, 3D hierarchical structures with high specific surface area (850 m2/g), abundant defect sites and thermal activation with microheaters.